Odpowiedzi

2009-11-24T16:05:52+01:00
Najlepsza Odpowiedź!
2009-11-24T16:10:29+01:00
A
2x-y=5
wiec
-y=5-2x /*(-1)
y=-5+2x

B
1y=x-3
wiec
y=x-3
C
3(x-y) = 2x wiec
3x-3y=2x
-3y=-x
y=(1/3)x
D
2 x = 3 y
y=(2/3)x

E
4x+2y=1
2y=1-4x
y=(1/2)-2x
F
6x - 2 y = 2
-2y=2-6x
y=-1+3x

1 5 1
2009-11-24T16:18:01+01:00
A..
2x-y=5
wiec
-y=5-2x /*(-1)
y=-5+2x

B..
1y=x-3
wiec
y=x-3
C..
3(x-y) = 2x wiec
3x-3y=2x
-3y=-x
y=(1/3)x

D..
2 x = 3 y
y=(2/3)x

E..
4x+2y=1
2y=1-4x
y=(1/2)-2x

F..
6x - 2 y = 2
-2y=2-6x
y=-1+3x